2011
DOI: 10.1117/12.877206
|View full text |Cite
|
Sign up to set email alerts
|

Deep space uplink receiver prototype for optical communications

Abstract: A hardware prototype of a flight receiver for deep space optical communications has been developed where a single detector array is used for acquisition, tracking, and high-speed data recovery. A counting algorithm accumulates pulses on every pixel in a photon-counting array and extracts signal information encoded with a nested modulation scheme.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
(3 reference statements)
0
2
0
Order By: Relevance
“…Lastly, photon-counting detectors have lower read-out noise than CCDs, especially at high frame readout rates. We have previously shown that a photon-counting detector allows centroiding estimates to be calculated with estimation errors close to the theoretical shot noise limit 4 . This serves to reduce the required transmitted power from Earth to acquire and track the uplink beacon.…”
Section: Introductionmentioning
confidence: 99%
“…Lastly, photon-counting detectors have lower read-out noise than CCDs, especially at high frame readout rates. We have previously shown that a photon-counting detector allows centroiding estimates to be calculated with estimation errors close to the theoretical shot noise limit 4 . This serves to reduce the required transmitted power from Earth to acquire and track the uplink beacon.…”
Section: Introductionmentioning
confidence: 99%
“…An example of this detector class is the Negative Avalanche Feedback Detector [8]. Using a small (6x6) photon counting focal plane array, we have demonstrated shot noise limited performance in centroid estimation [9]. The laser beacon can be modulated to allow background subtraction of scattered light and upwelling radiance from Earth.…”
Section: Architecturementioning
confidence: 99%